Sistem Komunikasi Interpersonal: Persepsi Interpersonal, Konsep Diri, Atraksi, dan Hubungan Interpersonal - Ahmad Fauzi Zainal Abidin; Muhammad Husnan Syadiidan; Umi Halwati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Interpersonal communication often fails not merely because of message ambiguity, but because of psychological barriers within communicators. This study aims to examine interpersonal communication as a systemic psychological process involving four interdependent elements: interpersonal perception, self-concept, interpersonal attraction, and relationship quality. Using a qualitative literature review, the study applies content analysis and theoretical synthesis to selected scholarly works published between 2020 and 2025. The findings show that interpersonal communication operates cyclically: perception shapes self-concept, self-concept influences attraction, attraction determines interaction intensity, and these processes affect relationship quality. Disruption in one element, such as biased perception or negative self-concept, can weaken the entire relational system. This study contributes a holistic conceptual framework that explains interpersonal communication beyond message clarity by emphasizing the role of psychological integration in building effective, supportive, and adaptive interpersonal relationships.